Telemedicine for Preoperative Assessment, Surgical Appointments, and Preoperative Education in Gynecological Day Surgery: An Prospective Observational Analysis - Wang Y; Xu G; Yan C; Wang F; Yang M; Wang Y (Dove Medical Press, 2024)
Yueqin Wang,* Gufeng Xu,* Chenqi Yan, Fang Wang, Min Yang, Yue Wang Department of Ambulatory Surgery, Women's Hospital, Zhejiang University School of Medicine, Hangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Yue Wang, Women's Hospital, Zhejiang University School of Medicine, Xueshi Road, Hangzhou, 310000, Zhejiang, People's Republic of China, Tel +86 87061501, Email Misswangyue@zju.edu.cnBackground: This study investigates the differences in the cost, time, pre-operative education and patient satisfaction levels of patients requiring a second hysteroscopic surgery using a full-service model of remote preoperative assessment, surgical appointments, and preoperative education.Methods: Forty-one patients who were proficient in the use of telemedicine platforms, planned to undergo a second hysteroscopic surgery, and selected either telemedicine (N=21) or face-to-face (N=20) models for their preoperative assessments, surgical appointments, and preoperative education were included. The data were analyzed using the Mann-Whitney U-test and Fisher's exact test.Results: No significant demographic differences were observed between patients who used telemedicine and those who did not. The telemedicine group demonstrated significantly lower median travel time (40 min vs 205 min, P < 0.01), time spent in hospital (60 min vs 155 min, P < 0.01), meal time (0 min vs 60 min, P < 0.01), and total time spent (108 min vs 415 min, P < 0.01). Similarly, the telemedicine group had significantly lower median travel expenses (40 yuan vs 300 yuan, P < 0.01) and meal expenses (0 yuan vs 135 yuan, P < 0.01), and overall, total expenses (255 yuan vs 837 yuan, P < 0.01). 95.2% of the telemedicine group completely understood the preoperative education, compared to 100% who completely understood in the face-to-face group (P = 1.00). All patients in the telemedicine group were very satisfied compared to 80% in the face-to-face group (P = 1.00).Conclusion: Telemedicine may be a feasible and advantageous method for preoperative assessment, surgical appointments, and preoperative education in gynecological day surgery. The application of telemedicine has demonstrated notable time and cost efficiency with high patient satisfaction levels. Future research should explore the full potential of telemedicine in this setting and for other surgical procedures.Keywords: telemedicine, gynecological day surgery, patient satisfaction, cost and time efficiency